Luis Xavier LÓPEZ-FARJEAT: ¿Qué sé?: Filosofía árabe islámica, México: Publicaciones Cruz O., S. A. 2007, 164 pp. - Diez, Casandra Fernández (Tópicos. Revista de Filosofía, 2013)
Luis Xavier LÓPEZ-FARJEAT: ¿Qué sé?: Filosofía árabe islámica, México: Publicaciones Cruz O., S. A. 2007, 164 pp.